Factors associated with parental literacy and hesitancy toward pediatric vaccination - Yi Zheng; Paula M. Frew; Dong Wang; Amanda L. Eiden (BMC Public Health)
Abstract Background Vaccine literacy (knowledge about vaccines and the ability to identify accurate information about them) and vaccine hesitancy (delay in or refusal of vaccination) among parents may affect immunization decision-making and pediatric vaccine uptake. This study aimed to examine the demographic and socioeconomic characteristics of parents by vaccine literacy and hesitancy and to assess the relationship between attitudinal, behavioral, and experiential factors and parents’ vaccine literacy and hesitancy. Methods A cross-sectional survey was administered in 2022 to US adults aged ≥ 18 (N = 692) who self-identified as parents/guardians of children aged < 18. Parents were asked questions about their experiences assessing information on pediatric vaccinations, their information-seeking and decision-making practices, interactions with healthcare providers (HCPs) regarding pediatric vaccines, beliefs about vaccine efficacy and safety, trust in scientific and medical information from various sources, perceptions of the danger and severity of vaccine-preventable diseases, and the benefits and convenience of vaccination. High vaccine literacy was defined as being moderately or extremely familiar with the vaccines a child should receive. Vaccine hesitancy was defined as being somewhat or very hesitant, or not sure, about childhood immunizations (i.e., shots). An exploratory factor analysis reflected 7 discrete underlying variables describing self-reported behaviors, beliefs, and experiences regarding childhood vaccination. Results Vaccine literacy and hesitancy were associated with parents’ gender, race/ethnicity, education level, and urbanicity. Factors associated with increased vaccine literacy were positive interactions with HCPs (OR 2.24, P < 0.001), active information-seeking behavior (OR 1.88, P < 0.001), positive beliefs about vaccines (OR 1.39, P = 0.001), and beliefs about vaccination requirements (OR 1.21, P = 0.041). Trouble understanding information from HCPs was associated with decreased vaccine literacy (OR 0.80, P = 0.025). Factors associated with decreased vaccine hesitancy were positive beliefs about vaccines (OR 0.41, P < 0.001), minimal concerns over childhood vaccines (OR 0.46, P < 0.001), and positive interactions with HCPs (OR 0.76, P = 0.002). Increased hesitancy was associated with negative beliefs about vaccines (OR 3.26, P < 0.001) and trouble understanding information from HCPs (OR 1.44, P < 0.001). Conclusions Greater vaccine literacy levels and less vaccine hesitancy correlated with positive parental beliefs about vaccines and positive interactions with HCPs. Challenges in comprehending HCP-delivered information were correlated with lower literacy and greater hesitancy.